Effect of infection with hepatitis B virus on the survival outcome of diffuse large B-cell lymphoma in the prophylactic antiviral era - Nuersulitan, Reyizha; Li, Miaomiao; Mi, Lan; Wu, Meng; Ji, Xinqiang; Liu, Yiqi; Zhao, Hong; Wang, Guiqiang; Song, Yuqin; Zhu, Jun; Liu, Weiping (Frontiers in Oncology, 2022)
Patients with lymphoma who are also infected with Hepatitis B virus (HBV) have a poor prognosis. This could be partly explained by the delay or premature termination of anti-tumor treatment because of HBV reactivation. However, there is limited data on the survival outcome of patients HBV-related lymphoma in the era of prophylactic antivirals. Data for 128 patients with HBV surface antigen-positive diffuse large B-cell lymphoma was collected. The median age was 54 years and the ratio of men to women was 1.2:1. All patients received immune-chemotherapy and prophylactic antiviral therapy. The median number of cycles of immune-chemotherapy was six. The overall response rate was 82%, with a complete remission rate of 75%. With a median follow-up of 58.4 months, the 5-year progression-free survival and overall survival rates were 75.7% and 74.7%, respectively. Nine patients experienced HBV reactivation but none experienced HBV-associated hepatitis. Patients with low and high HBV DNA loads had comparable survival outcomes. In conclusion, HBV infection had no negative effect on the prognosis of DLBCL in the era of prophylactic antiviral therapy.